Safety and Comfortableness of Playing as the Manifestation of Child Friendly Kampung. Case Study of Kampung Badran Yogyakarta - Hastuti Saptorini; Heri Apricilianingtyas (Departement of Architecture, Universitas Islam Indonesia, 2017)
Limited space in densely populated area in cities becomes threat for safety and comfortableness for children need for outdoor playground. Kampung Badran in Yogyakarta has been declared as one of the children friendly kampungs. Thus, it is necessary to examine the parameters and indicators of safety and comfortableness to move based on the standard. This paper aims to study the level of safety and comfortableness in the playing space of children in the kampung as the manifestation of children friendly kampung. The data was collected by observing and taking photographs and analyzed with descriptive analytical method. The findings show that the conditions of facilities in the form of space are relatively adequate and safe. However, the condition of playing equipment and facilities are not safe and lacking of treatment. The children who are playing are prone to potential accidents such as sinking in, jammed in, and slippery. The participation of stakeholders in maintaining and developing the Kampung is highly needed because the kampung has potential assets to be example and role model for other kampung to achieve Children Friendly Kampong.Key Words: children safety, movement comfortableness, children friendly Kampung